2018
DOI: 10.4995/wrs.2018.7373
|View full text |Cite
|
Sign up to set email alerts
|

Preference of rabbit does among different nest materials

Abstract: Nest quality is important for the survival of new-born rabbits. Nesting material in rabbit farms generally consists of wood shavings, which is completely different from the dry grass used by the European wild rabbit (<em>Oryctolagus cuniculus</em>). The aim of the experiments was to examine which nest materials are preferred by rabbit does when building their nest. In experiment 1, the choice of multiparous rabbit does (n=37) among nest boxes bedded with different nesting materials was monitored. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…They found a positive correlation between burrow-digging and elevated progesterone levels as well as increased intraspecific aggressive behavior in response to administered progesterone. A similar phenomenon was described by Farkas, et al [35], who successfully identified two peaks in relation to the gathering of nest material in domesticated rabbits. The first peak designating the carrying of nesting material, was on days 27 and 28, nearly identical to the normal (LR) does in our experiment.…”
Section: Plos Onesupporting
confidence: 79%
“…They found a positive correlation between burrow-digging and elevated progesterone levels as well as increased intraspecific aggressive behavior in response to administered progesterone. A similar phenomenon was described by Farkas, et al [35], who successfully identified two peaks in relation to the gathering of nest material in domesticated rabbits. The first peak designating the carrying of nesting material, was on days 27 and 28, nearly identical to the normal (LR) does in our experiment.…”
Section: Plos Onesupporting
confidence: 79%
“…Farkas et al. () concluded that rabbit does showed the following preference for nest materials: Lignocel ® (fine fibre material for pet animals made of wood) > straw > hay > wood shavings. Based on literature, although rabbit does may have different preferences for the nesting materials mentioned above, they can express their normal maternal behaviour whatever the nesting material.…”
Section: Assessmentmentioning
confidence: 99%
“…Cottontail rabbit (Sylvilagus floridanus) females were also seen collecting dry long grass and forming an outer grass layer lining the excavated nest cavity [56]. In Blumetto et al [52] studies, mother rabbits preferred straw to wood chips as a nesting material, and elongated dry material was also preferred in a highly inbred rabbit stock [35]. The functional significance of using dry grass as nest material is not yet fully understood, heat insulation property [2,13,53,57] or/and its high capacity to bind water [53] are likely candidate features enhancing the survival of wild rabbit kits developing in a closed underground chamber for weeks [18].…”
Section: Discussionmentioning
confidence: 99%
“…The functional significance of using dry grass as nest material is not yet fully understood, heat insulation property [2,13,53,57] or/and its high capacity to bind water [53] are likely candidate features enhancing the survival of wild rabbit kits developing in a closed underground chamber for weeks [18]. Even though it might be problematic to incorporate hay as a nest material in rabbit production systems [35] as fungal toxins can induce health issues [58,59], the welfare status can be improved by mimicking natural situations in the rearing environment [60][61][62] In summary, by performing laboratory experiments to understand the functional significance of the preference of wild rabbits for dry elongated grass nest material we found that, similarly to their wild ancestors, even unexperienced domestic rabbit females collect dry and long grass preferentially. The even larger proportion of dry grass found in the final nests and occasional observations of the does in the nest chamber suggest a modification of the nest composition after the collection phase by eating some of the green grass (see Experiment 2 and 3), and thus the final composition of the nests was strikingly uniform and similar to the composition of the nests found in the field and made by the wild ancestors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation